Effects of Abiotic Stress Associated with Climate Change on Potato Yield and Tuber Quality Under a Multi-environment Trial in New Zealand - Siano AB; Roskruge N; Kerckhoffs H; Sofkova-Bobcheva S (Springer Nature, 2024)
In the 2018/19 growing season, a multi-environment trial in Opiki, Hastings, and Ohakune located in three different regions of the North Island of New Zealand was conducted to evaluate responses of selected potato cultivars to abiotic stress associated with climate change. Heat and drought stresses were evident with supra-optimal temperatures (> 25 °C) in Opiki and Hastings and sub-optimal rainfall (< 500 mm) in Opiki, which influenced the different morpho-physiological characteristics of the potato crop, ultimately affecting yield and tuber quality. These abiotic stresses also increased the incidence of malformation, growth cracks, and second growth in tubers reducing the total and marketable tuber yields by 43% and 45%, respectively. In addition, the genotype × environment analysis showed that Ohakune had the most favourable environmental conditions for potato production since all cultivars in this site had superior marketable tuber yields. ‘Taurus’ was the most stable and adaptable cultivar across trial sites (wide adaptation), whilst ‘Hermes’ and ‘Snowden’ were more adapted under Opiki and Hastings conditions (specific adaptation), respectively. As established in this study, heat and drought stresses have significant effects on the morpho-physiology, yield, and tuber quality of commercial potato cultivars in New Zealand.
Keywords: Climate adaptation; Drought stress; Genotype; Heat stress; Marketable tuber yield; Physiological disorders